Analisis Rantai Nilai Agroindustri Gula Aren Murni dan Campuran di Kecamatan Rambah, Kabupaten Rokan Hulu, Indonesia: Value Chain Analysis for Pure and Mixed Palm Sugar Agroindustry in Rambah District, Rokan Hulu Regency, Indonesia - Astuti, Nesri; Dewi, Novia; Maharani, Evy (Journal of Integrated Agribusiness, 2025)
Palm sugar is a processed product derived from the sap of palm trees, which is boiled and molded into solid sugar. This study aims to (1) identify the value chain and (2) analyze the margin and efficiency of value chain patterns in Rambah District, Rokan Hulu Regency. A purposive sampling method was employed, involving six respondents. Data analysis included value chain mapping as well as margin and efficiency calculations. The findings reveal two value chain patterns for both pure and mixed palm sugar agroindustries. The main activities in the value chain consist of inbound logistics, operations, outbound logistics, marketing and sales, and services. Supporting activities include procurement, infrastructure, human resource management, and technology development. In the pure palm sugar agroindustry, Pattern I yields a value chain margin of IDR 14,797.50 with an efficiency of 8.68%, while Pattern II yields a margin of IDR 18,959.09 with an efficiency of 8.70%. In the mixed palm sugar agroindustry, Pattern I generates a margin of IDR 6,000 with an efficiency of 12.23%, whereas Pattern II produces a margin of IDR 7,000 with an efficiency of 12.63%.